Analysis of energy costs in granulators - Komar, Artem; Комар, Артем Станіславович (Запоріжжя: ТДАТУ, 2026)
In today's highly employed environment, granulated/tableted products are becoming increasingly popular, as they improve the transportability of bulk raw materials, reduce caking, and prevent segregation of multi-component mixtures. Granulators are the key components in the production of such products.
Keywords: energy; granulated/tableted products